Interference effects of different resistance-training protocols on rowing ergometer performance: a study on semiprofessional rowers - Janicijevic, D.; Quidel-Catrilelbún, M. E. L.; Baena-Raya, A.; García-Ramos, A. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To evaluate the interference effects of various resistance-training (RT) protocols on rowing ergometer performance. Methods: Fourteen semiprofessional male rowers randomly completed 5 protocols in separate sessions: (1) control—no RT session was performed, (2) upper-body high-fatigue—4 sets to failure during the bench pull exercise, (3) upper-body low-fatigue—4 sets of 6 repetitions during the bench pull exercise, (4) lower-body high-fatigue—4 sets to failure during the leg-press exercise, and (5) lower-body low-fatigue—4 sets of 6 repetitions during the leg-press exercise. All sets were performed against the 12-repetition-maximum load with 2 minutes of interset rest. Following the completion of the protocols, subjects performed an all-out 1000-m rowing ergometer test. Results: Compared with the control condition, rowing ergometer performance was not significantly affected after the low-fatigue RT protocols (upper body: P = .487; Delta = 0.0%-0.2%; lower body: P = .200; Delta = -0.2%-0.5%), while it significantly declined following high-fatigue RT protocols (upper body: P = .001; delta = 1.0%-2.0%; lower body: P = .002; delta = 2.1%-2.5%). The average heart rate was significantly lower for the control condition compared with all RT protocols (P = .043; delta = 1.0%-1.5%). Conclusions: To minimize interference on rowing performance, coaches should prioritize the level of effort in RT protocols over specific exercises, specifically avoiding high-fatigue protocols that lead to failure before rowing practice.